Solid oxide battery and manufacturing method thereof
By using hollow particles to form a porous structure fuel electrode, the problem of stability of the fuel electrode pore structure at high temperature is solved, and the stable redox reaction of solid oxide batteries at high temperature is achieved.
Patent Information
- Application Number
- CN202380056804.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-05
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-11
AI Technical Summary
It is difficult for existing solid oxide batteries to maintain the pore structure of the fuel electrode at high temperatures, which affects the stability of the redox reaction.
Hollow particles are used as fuel electrode material, wherein the particles include cores with empty spaces and shells of nickel oxide particles, forming a porous structure without the need for a pore-forming agent.
The three-phase interface in which water can decompose smoothly in electrochemical reactions is ensured, the structural stability of the fuel electrode is maintained, and a stable redox reaction is performed at high temperatures.
Smart Images

Figure CN119605004A_ABST
Abstract
Description
Technical Field
[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0159245 filed on November 24, 2022, in the Korean Intellectual Property Office, and Korean Patent Application No. 10-2023-0044925 filed on April 5, 2023, in the Korean Intellectual Property Office, the entire contents of which are incorporated herein by reference.
[0002] The present disclosure relates to a solid oxide battery and a method for manufacturing the same. Background Art
[0003] Solid oxide fuel cells (SOFCs) and solid oxide electrolyzers (SOECs) generate electrical energy through an electrochemical reaction of a cell (the cell is composed of an air electrode, a fuel electrode, and a solid oxide electrolyte having oxygen ion conductivity) or electrolyze water and generate hydrogen through the reverse reaction of a solid oxide fuel cell. The cell has a structure in which an air electrode and a fuel electrode are respectively arranged at both sides of a solid oxide electrolyte having oxygen ion conductivity, wherein air and hydrogen are respectively supplied to the air electrode and the fuel electrode through an air flow path formed on a separator to perform an electrochemical reaction to generate electricity or perform electrolysis.
[0004] In particular, the solid oxide electrolytic cell operates at 800° C. or higher, and therefore requires material properties that are stable in oxidation / reduction reactions at high temperatures. In addition, the fuel electrode needs to have a pore structure through which water can diffuse and move well. Summary of the invention
[0005] Technical issues
[0006] One aspect of the present disclosure provides a solid oxide cell that forms a fuel electrode having a pore structure without a pore former, thereby ensuring a three-phase interface in which water can be smoothly decomposed through an electrochemical reaction, maintaining the structure during firing, and performing a stable redox reaction at a high temperature.
[0007] Technical Solution
[0008] According to one aspect, a solid oxide battery includes: a solid oxide electrolyte; a fuel electrode located on one side of the solid oxide electrolyte, the fuel electrode including hollow particles, the hollow particles including a core having an empty space and a shell including nickel oxide (NiO) particles; and an air electrode located on the other side of the solid oxide electrolyte.
[0009] The hollow particles may have a spherical shape.
[0010] The hollow particles may have an average particle diameter of 1 μm to 10 μm.
[0011] The fuel electrode may also include a solid oxide electrolyte material.
[0012] The solid oxide electrolyte material may include yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), or a combination thereof.
[0013] The solid oxide electrolyte material may be in the form of particles having an average particle size of 3 μm to 20 μm.
[0014] The fuel electrode may include 30 to 70 parts by weight of the hollow particles based on 100 parts by weight of the solid oxide electrolyte material.
[0015] The fuel electrode may also include a fuel electrode material including nickel (Ni), nickel oxide, cobalt (Co), cobalt oxide, ruthenium (Ru), ruthenium oxide, palladium (Pd), palladium oxide, platinum (Pt), platinum oxide, or a combination thereof.
[0016] The fuel electrode material may be in the form of particles having an average particle size of 0.1 μm to 5 μm.
[0017] The fuel electrode may include 30 parts by weight to 70 parts by weight of the fuel electrode material based on 100 parts by weight of the solid oxide electrolyte material.
[0018] The solid oxide electrolyte may include yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), or a combination thereof.
[0019] The air electrode may include lanthanum strontium manganese oxide (LSM), lanthanum strontium iron oxide (LSF), lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt iron oxide (LSCF), samarium strontium cobalt oxide (SSC), barium strontium cobalt iron oxide (BSCF), bismuth ruthenium oxide, or a combination thereof.
[0020] The air electrode may also include a solid oxide electrolyte material.
[0021] The solid oxide cell may be a solid oxide fuel cell (SOFC), a solid oxide electrolyzer (SOEC), or both.
[0022] A method of manufacturing a solid oxide cell according to another aspect of the present disclosure includes forming a fuel electrode from a composition including hollow particles including a core having a hollow space and a shell including nickel oxide (NiO) particles.
[0023] The composition may further include a solid oxide electrolyte material.
[0024] The composition may also include a fuel electrode material.
[0025] The composition for forming the fuel electrode may include 30 to 70 parts by weight of hollow particles based on 100 parts by weight of the solid oxide electrolyte material.
[0026] The composition for forming the fuel electrode may include 30 parts by weight to 70 parts by weight of the fuel electrode material based on 100 parts by weight of the solid oxide electrolyte material.
[0027] The step of forming the fuel electrode may include casting the composition and then firing the cast composition.
[0028] According to one aspect, a solid oxide cell includes: a solid oxide electrolyte; a fuel electrode located on one side of the solid oxide electrolyte, the fuel electrode including a fuel electrode material and hollow particles, the hollow particles including a core having an empty space and a shell including nickel oxide (NiO) particles; and an air electrode located on the other side of the solid oxide electrolyte.
[0029] The fuel electrode may also include a solid oxide electrolyte material.
[0030] The fuel electrode may include 30 to 70 parts by weight of the hollow particles based on 100 parts by weight of the solid oxide electrolyte material.
[0031] The fuel electrode material may include nickel (Ni), nickel oxide, cobalt (Co), cobalt oxide, ruthenium (Ru), ruthenium oxide, palladium (Pd), palladium oxide, platinum (Pt), platinum oxide, or a combination thereof.
[0032] The fuel electrode may include 30 parts by weight to 70 parts by weight of the fuel electrode material based on 100 parts by weight of the solid oxide electrolyte material.
[0033] The shell may be free of other metal oxides.
[0034] Beneficial effects
[0035] According to a solid oxide cell according to one aspect, a three-phase interface in which water can be smoothly decomposed by an electrochemical reaction can be ensured by forming a porous fuel electrode without a pore former to maintain a structure during firing and perform a stable redox reaction at a high temperature. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 is a diagram schematically illustrating a cross section of a solid oxide cell according to one aspect.
[0037] Figure 2 is a scanning electron microscope (SEM) photograph of hollow particles.
[0038] Figure 3 This is a transmission electron microscope (TEM) photograph of hollow particles.
[0039] Figure 4 is a schematic diagram showing a solid oxide fuel cell according to a modified embodiment of an aspect.
[0040] Figure 5 is a schematic diagram showing a solid oxide water electrolysis cell according to another variant embodiment of the one aspect. DETAILED DESCRIPTION
[0041] Hereinafter, the present disclosure will be described in detail with reference to the accompanying drawings so that a person of ordinary skill in the art can practice. The drawings and descriptions are considered to be illustrative rather than restrictive in nature. Throughout the specification, the same reference numerals represent the same elements. In addition, the drawings are provided only to make the disclosed embodiments in this specification easy to understand, and are not to be construed as limiting the spirit disclosed in this specification, and it should be understood that the present disclosure includes all variations, equivalents and alternatives without departing from the scope and spirit of the present disclosure. In addition, some components are exaggerated, omitted or schematically depicted in the drawings, and the size of each component does not necessarily represent the actual size.
[0042] In addition, unless explicitly described to the contrary, the word “comprise” and variations such as “including” or “having”, will be understood to imply the inclusion of stated elements but not the exclusion of any other elements.
[0043] As disclosed herein, a particle size analyzer may be used to obtain the average particle size. Even if not described in the present disclosure, other methods and / or tools understood by those of ordinary skill in the art may also be used.
[0044] Figure 1 is a diagram schematically illustrating a cross section of a solid oxide cell according to one aspect.
[0045] Reference Figure 1 , the solid oxide cell 100 includes: a solid oxide electrolyte 130; a fuel electrode 110 disposed on one side of the solid oxide electrolyte 130; and an air electrode 120 disposed on the other side.
[0046] The fuel electrode 110 is used to electrochemically oxidize the fuel and transfer charges. Therefore, the fuel electrode 110 requires a pore structure that allows the diffusion of the fuel to proceed smoothly.
[0047] In the case where a pore former such as a spherical polymer or a carbon material is mixed, molded and printed in order to ensure pores in the fuel electrode 110, and then heat-treated to form a pore structure by decomposing the pore former, when preparing a slurry or paste for molding and printing, it is not easy to control the pores due to the uniform dispersion of the pore former and its change over time, and there is a possibility that the pore structure will collapse when the pore former is decomposed by heat treatment.
[0048] In a solid oxide cell 100 according to one aspect, a fuel electrode 110 includes a core-shell hollow particle 111 in which a core has an empty space and a shell includes a nickel oxide (NiO) particle. For example, the hollow particle 111 is a secondary particle formed by agglomeration of nickel oxide particles as primary particles, and may include an empty space therein. That is, the hollow particle 111 may have a core-shell shape in which a core has an empty space and a shell includes a nickel oxide particle.
[0049] In other words, the fuel electrode 110 includes nickel oxide particles having a hollow core structure and may have a pore structure without a pore former, thereby ensuring a three-phase interface on which the fuel can be smoothly decomposed by an electrochemical reaction. In addition, nickel oxide, which is a stable material at high temperatures, maintains a pore structure during firing and is stable in oxidation / reduction reactions at high temperatures.
[0050] Figure 2 is a scanning electron microscope (SEM) photograph of the hollow particle 111, and Figure 3 is a transmission electron microscope (TEM) photograph of the hollow particle 111.
[0051] Reference Figure 2 and Figure 3 , the hollow particles 111 may have a substantially spherical shape. However, the solid oxide battery 100 according to the present aspect is not limited thereto, but the hollow particles 111 may have, for example, a spherical shape, a polyhedral shape, etc. in overall cross section.
[0052] The hollow particles 111 may have an average particle size of 1 to 10 μm. When the hollow particles 111 have an average particle size less than 1 μm, the pores are too small to ensure a smooth pore structure, and when the average particle size is greater than 10 μm, the mechanical strength may be weakened due to excessive pores.
[0053] The fuel electrode 110 may also include a solid oxide electrolyte material 113 .
[0054] The solid oxide electrolyte material 113 should have high oxygen ion conductivity and low electron conductivity.
[0055] For example, the solid oxide electrolyte material 113 may include yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), or a combination thereof.
[0056] The solid oxide electrolyte material 113 may be in the form of particles having an average particle size of 3 μm to 20 μm. When the average particle size of the solid oxide electrolyte material 113 is less than 3 μm, ion conductivity may be deteriorated due to a small grain size after sintering, and when the average particle size of the solid oxide electrolyte material 113 is greater than 20 μm, sinterability may be reduced, deteriorating density.
[0057] When the fuel electrode 110 may include 30 to 70 parts by weight of the hollow particles 111 based on 100 parts by weight of the solid oxide electrolyte material 113. When the amount of the hollow particles 111 included is less than 30 parts by weight, the content of the fuel electrode material is insufficient, deteriorating the electrical characteristics, and when the amount of the hollow particles 111 included is greater than 70 parts by weight, the content of the solid oxide electrolyte material is insufficient, deteriorating the ion conductivity.
[0058] The fuel electrode 110 may further include a fuel electrode material 112. The fuel electrode material 112 may electrochemically oxidize the fuel and transfer charges.
[0059] For example, the fuel electrode material 112 may include pure metals such as nickel (Ni), cobalt (Co), ruthenium (Ru), palladium (Pd), or platinum (Pt), or oxides thereof.
[0060] Herein, the fuel electrode 110 may include a cermet as a composite of a fuel electrode material 112 and a solid oxide electrolyte material 113. For example, when the solid oxide electrolyte material 113 is yttria-stabilized zirconia (YSZ) and the fuel electrode material 112 is nickel (Ni), the porous solid oxide composite may be a Ni / YSZ cermet, and when the fuel electrode material 112 is ruthenium (Ru), the porous solid oxide composite may be a Ru / YSZ cermet.
[0061] The fuel electrode material 112 may have an average particle size of 0.1 μm to 5 μm or 0.5 μm to 5 μm. When the average particle size of the fuel electrode material 112 is less than 0.1 μm, the fuel electrode material itself is difficult to connect, which deteriorates the electronic conductivity. When the average particle size of the fuel electrode material 112 is greater than 5 μm, the active specific surface area is reduced, which deteriorates the electrical properties.
[0062] The fuel electrode 110 may include 30 to 70 parts by weight of the fuel electrode material 112 based on 100 parts by weight of the solid oxide electrolyte material 113. When the amount of the included fuel electrode material 112 is less than 30 parts by weight, ion conductivity may be deteriorated, and when the amount of the included fuel electrode material 112 is greater than 70 parts by weight, electron conductivity may be deteriorated.
[0063] For example, the thickness of the fuel electrode 110 may be, for example, 1 μm to 1000 μm or 5 μm to 100 μm.
[0064] The porosity of the fuel electrode 110 may be 20% to 60%. When the porosity of the fuel electrode 110 is less than 20%, mass flow resistance of raw materials and generated gas may increase, and when the porosity of the fuel electrode 110 is greater than 60%, mechanical strength may deteriorate.
[0065] The air electrode 120 includes an air electrode material. The air electrode material may be a material that reduces oxygen to oxygen ions.
[0066] For example, the air electrode material may include metal oxide particles having a perovskite crystal structure. Perovskite metal oxides are mixed ion electron conductor (MIEC) materials having both ion conductivity and electronic conductivity, and have high oxygen diffusion coefficients and charge exchange reaction rate coefficients, allowing redox reactions to occur over the entire surface of the electrode, rather than just at the three-phase interface.
[0067] The perovskite type metal oxide may be represented by Chemical Formula 1.
[0068] [Chemical formula 1]
[0069] ABO 3±γ
[0070] In Chemical Formula 1, A is an element including La, Ba, Sr, Sm, Gd, Ca, or a combination thereof, B is an element including Mn, Fe, Co, Ni, Cu, Ti, Nb, Cr, Sc, or a combination thereof, and γ represents oxygen excess or oxygen deficiency. For example, γ may be in the range of 0≤γ≤0.3.
[0071] For example, the perovskite type metal oxide may be represented by Chemical Formula 2.
[0072] [Chemical formula 2]
[0073] A' 1-x A” x B'O 3±γ
[0074] In Chemical Formula 2, A′ is an element including Ba, La, Sm or a combination thereof, A″ is an element including Sr, Ca, Ba or a combination thereof and is different from A′, B′ is an element including Mn, Fe, Co, Ni, Cu, Ti, Nb, Cr, Sc or a combination thereof, 0≤x<1, and γ represents oxygen excess or oxygen deficiency.
[0075] For example, the air electrode material may include lanthanum strontium manganese oxide (LSM), lanthanum strontium iron oxide (LSF), lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt iron oxide (LSCF), samarium strontium cobalt oxide (SSC), barium strontium cobalt iron oxide (BSCF), bismuth ruthenium oxide, or combinations thereof.
[0076] In this case, if the solid oxide electrolyte material is yttria stabilized zirconia (YSZ) and the air electrode material may be lanthanum strontium manganese oxide (LSM), the porous solid oxide composite may be a LSM-YSZ composite.
[0077] For example, the thickness of the air electrode 120 may be 1 μm to 100 μm or 5 μm to 50 μm.
[0078] The solid oxide electrolyte 130 plays a role in transporting the generated oxygen ions from the air electrode 120 to the fuel electrode 110 by ion conduction. The solid oxide electrolyte 130 has airtightness to prevent contact between the air and the fuel electrode 110, and also prevents the electrons generated at the fuel electrode 110 from moving directly toward the air electrode 120 due to high oxygen ion conductivity and low electron conductivity (high resistance, high insulation).
[0079] In addition, since the solid oxide electrolyte 130 has the air electrode 120 and the fuel electrode 110 on both sides thereof, which have a very large oxygen partial pressure difference, the aforementioned properties may need to be maintained in a wide oxygen partial pressure region.
[0080] The material constituting the solid oxide electrolyte 130 is not particularly limited as long as it is generally used in the art, and examples thereof may include yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), or a combination thereof.
[0081] For example, the thickness of the solid oxide electrolyte 130 may be 10 nm to 100 μm or 100 nm to 50 μm.
[0082] Optionally, the solid oxide cell 100 may further include a current collecting layer (not shown) including an electrical conductor located on at least one side of the air electrode 120 (e.g., the outside of the air electrode 120). The current collecting layer may serve as a current collector to collect electricity in the configuration of the air electrode 120.
[0083] The collector layer may include, for example, lanthanum cobalt oxide (LaCoO3), lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt iron oxide (LSCF), lanthanum strontium cobalt manganese oxide (LSCM), lanthanum strontium manganese oxide (LSM), lanthanum strontium iron oxide (LSF), or a combination thereof. The collector layer may use the materials listed above alone or in a combination of two or more, wherein these materials may be formed into a single layer or two or more layers having a stacked structure.
[0084] The solid oxide cell 100 may be applied to various structures, such as a cylindrical (tubular) stack, a flat tubular stack, a planar stack, and the like.
[0085] In addition, the solid oxide cell 100 may be in the form of a unit cell stack. For example, unit cells (membrane electrode assembly (MEA)) composed of air electrodes 120 and 310, fuel electrode 110 and solid oxide electrolyte 130 are stacked in series, and electrically connected separators are provided between the unit cells to obtain a unit cell stack.
[0086] For example, the solid oxide cell 100 may be a solid oxide fuel cell (SOFC), a solid oxide electrolyzer (SOEC), or both.
[0087] Figure 4 1 is a schematic diagram showing a case where the solid oxide cell 100 is a solid oxide fuel cell.
[0088] Reference Figure 4The solid oxide fuel cell 200 includes: a fuel electrode 210; an air electrode 220 disposed facing the fuel electrode 110; and an oxygen ion conductive solid oxide electrolyte 230 disposed between the fuel electrode 210 and the air electrode 220.
[0089] The solid oxide fuel cell 200 has an electrochemical reaction as shown in Reaction Formula 1, which shows that oxygen (O2) at the air electrode 220 is converted into oxygen ions (O2 - ) and a fuel electrode reaction in which the fuel (H2 or hydrocarbon) of the fuel electrode 210 reacts with oxygen ions passing through and into the electrolyte.
[0090] [Reaction formula 1]
[0091] Air electrode reaction: 1 / 2O2+2e - →O2 -
[0092] Fuel electrode reaction: H2+O2 - →H2O+2e -
[0093] In the air electrode 220 of the solid oxide fuel cell 200, oxygen adsorbed into the electrode surface is dispersed and moves through surface diffusion to the three-phase interface (three-phase boundary) where the solid oxide electrolyte 230, the air electrode 220 and the pores (not shown) intersect to obtain electrons to become oxygen ions, and the generated oxygen ions move toward the fuel electrode 210 through the solid oxide electrolyte 230.
[0094] In the fuel electrode 210 of the solid oxide fuel cell 200, the moving oxygen ions combine with the hydrogen in the fuel to generate water. At this time, the hydrogen releases electrons to become hydrogen ions (H + ) is combined with oxygen ions. The released electrons move toward the air electrode 220 through a wire (not shown) to change oxygen into oxygen ions. Through this electron movement, the solid oxide fuel cell 200 can perform a battery function.
[0095] Figure 5 Schematic diagram showing a case where the solid oxide cell 100 is a solid oxide electrolytic cell.
[0096] Reference Figure 5 The solid oxide electrolysis cell 300 includes: an air electrode 310; a fuel electrode 320 disposed facing the air electrode 310; and an oxygen ion conductive solid oxide electrolyte 330 disposed between the air electrode 310 and the fuel electrode 320.
[0097] The solid oxide electrolysis cell 300 has an electrochemical reaction shown in Reaction Formula 2, which shows that water (H2O) at the fuel electrode 320 is converted into hydrogen (H2) and oxygen ions (O2 - ) and an air electrode reaction in which oxygen ions passing through the solid oxide electrolyte 330 are converted into oxygen (O2). This reaction is opposite to the reaction principle of a conventional fuel cell.
[0098] [Reaction 2]
[0099] Fuel electrode reaction: H2O+2e - →O2 - +H2
[0100] Air electrode reaction: O2 - →1 / 2O2+2e -
[0101] When power is applied to the solid oxide electrolysis cell 300 from the external power supply 340, the solid oxide electrolysis cell 300 is supplied with electrons from the external power supply 340. The electrons react with the water supplied to the fuel electrode 320 to generate hydrogen and oxygen ions. The hydrogen is released to the outside, and the oxygen ions pass through the electrolyte 330 to reach the air electrode 310. The oxygen ions moved to the air electrode 310 lose electrons and then become oxygen and are released to the outside. The electrons flow to the external power supply 340. Through this electron movement, the solid oxide electrolysis cell 300 can electrolyze water to form hydrogen at the fuel electrode 320 and oxygen at the air electrode 310.
[0102] A method of manufacturing a solid oxide cell according to another aspect includes: forming a fuel electrode; forming a solid oxide electrolyte on the fuel electrode; and forming an air electrode on the solid oxide electrolyte.
[0103] The fuel electrode can be manufactured by casting the composition for forming the fuel electrode into, for example, a sheet shape and then firing the resultant.
[0104] The composition for forming the fuel electrode includes a core-shell hollow particle in which the core has an empty space and the shell includes nickel oxide (NiO) particles, and optionally, a solid oxide electrolyte material, a fuel electrode material, or a combination thereof. Since the description of the hollow particles, the solid oxide electrolyte material, and the fuel electrode material is the same as the hollow particles, the solid oxide electrolyte material, and the fuel electrode material described above, repeated description will be omitted.
[0105] However, hollow particles can be made by template synthesis. The template can be made from spherical shaped particles such as polymers, silicon dioxide (SiO2) or carbon.
[0106] Additionally, the composition for forming a fuel electrode may optionally further include a dispersant, a plasticizer, a binder, a solvent, etc., and may be in the form of a slurry, a paste, or a dispersion.
[0107] The composition for forming a fuel electrode may be cast into a sheet shape by a wet method (eg, a dipping method, a coating method, a printing method, a spraying method, etc.).
[0108] The composition for forming the fuel electrode may include 30 to 70 parts by weight of hollow particles based on 100 parts by weight of the solid oxide electrolyte material. When the amount of the hollow particles included is less than 30 parts by weight, the content of the fuel electrode material is insufficient, deteriorating the electrical characteristics, and when the amount of the hollow particles included is greater than 70 parts by weight, the content of the solid oxide electrolyte material is insufficient, deteriorating the ion conductivity.
[0109] The composition for forming the fuel electrode may include 30 to 70 parts by weight of the fuel electrode material based on 100 parts by weight of the solid oxide electrolyte material. When the amount of the included fuel electrode material is less than 30 parts by weight, the ion conductivity may be deteriorated, and when the amount of the included fuel electrode material is greater than 70 parts by weight, the electronic conductivity may be deteriorated.
[0110] For example, firing may be performed at 1000° C. to 1500° C. (e.g., 1300° C. to 1500° C. or 1400° C. to 1450° C.) in an air atmosphere. However, the method of manufacturing a solid oxide battery according to the present aspect is not limited thereto, but firing of the fuel electrode may be performed together with the solid oxide electrolyte after forming the solid oxide electrolyte.
[0111] For example, the solid oxide electrolyte may be formed by casting the composition for a solid oxide electrolyte into a sheet shape on a fuel electrode and then firing it.
[0112] The composition for solid oxide electrolyte may include solid oxide electrolyte material. The description of solid oxide electrolyte material may be the same as above and will not be repeated. In addition, optionally, the composition for solid oxide electrolyte may include dispersant, plasticizer, binder, solvent, etc., and may be in the form of slurry, paste or dispersion.
[0113] The composition for a solid oxide electrolyte may be cast into a sheet shape by a wet method (eg, dipping, coating, printing, spraying, etc.) For example, the composition for a solid oxide electrolyte may be cast on a fuel electrode.
[0114] For example, firing may be performed at 1000° C. to 1500° C. (eg, 1300° C. to 1500° C. or 1400° C. to 1450° C.) in an air atmosphere.
[0115] For example, the air electrode may be formed by casting the composition for the air electrode into a sheet shape and then firing it.
[0116] The composition for the air electrode may include an air electrode material and a solid oxide electrolyte material. The description of the air electrode material and the solid oxide electrolyte material is the same as above and will not be repeated. In addition, optionally, the composition for the air electrode may also include a dispersant, a plasticizer, a binder or a solvent, etc., and may be in the form of a slurry, a paste or a dispersion.
[0117] The composition for an air electrode may be cast into a sheet shape by a wet method (eg, an impregnation method, a coating method, a printing method, a spraying method, etc.), and may be cast into a sheet shape on a solid oxide electrolyte.
[0118] For example, the firing may be performed at 1000° C. to 1500° C. (eg, 1300° C. to 1500° C. or 1400° C. to 1450° C.) in an air atmosphere.
[0119] In the above, it is described that a solid oxide electrolyte is formed on a fuel electrode and an air electrode is sequentially formed on the solid oxide electrolyte, but the method of manufacturing a solid oxide cell according to the present aspect is not limited to this, but the fuel electrode, the air electrode and the solid oxide electrolyte may be manufactured separately and then stacked, or after forming a solid oxide electrolyte on the air electrode, the fuel electrode may be sequentially formed on the solid oxide electrolyte.
[0120] In addition, it is described that firing is performed after forming a fuel electrode, after forming a solid oxide electrolyte, and after forming an air electrode, respectively, but the method for manufacturing a solid oxide cell according to the present aspect is not limited to this, and after forming a solid oxide electrolyte on the fuel electrode, an air electrode may be formed on the solid oxide electrolyte and then fired at the same time, or a solid oxide electrolyte may be formed on the fuel electrode and then fired, and an air electrode may be formed thereon and then fired.
[0121] While the present disclosure has been described in conjunction with what are presently considered to be practical example embodiments, it should be understood that the present disclosure is not limited to the disclosed embodiments, but is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
[0122] Industrial Applicability
[0123] The present disclosure relates to a solid oxide cell and a method for manufacturing the same, and the solid oxide cell forms a fuel electrode having a pore structure without a pore former, thereby ensuring a three-phase interface in which water can be smoothly decomposed by an electrochemical reaction, maintaining the structure during firing, and performing a stable redox reaction at a high temperature.
Claims
1. A solid oxide battery comprising: Solid oxide electrolytes; a fuel electrode located on one side of the solid oxide electrolyte, the fuel electrode including hollow particles including a core having an empty space and a core including nickel oxide (NiO) particles; and An air electrode is located on the other side of the solid oxide electrolyte.
2. The solid oxide battery according to claim 1, wherein: The hollow particles have a spherical shape.
3. The solid oxide battery according to claim 1, wherein: The hollow particles have an average particle diameter of 1 μm to 10 μm.
4. The solid oxide battery according to claim 1, wherein: The fuel electrode also includes a solid oxide electrolyte material.
5. The solid oxide battery according to claim 4, wherein: The solid oxide electrolyte material includes yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), or a combination thereof.
6. The solid oxide battery according to claim 4, wherein: The solid oxide electrolyte material is in the form of particles having an average particle size of 3 μm to 20 μm.
7. The solid oxide battery according to claim 4, wherein: The fuel electrode includes 30 to 70 parts by weight of the hollow particles based on 100 parts by weight of the solid oxide electrolyte material.
8. The solid oxide battery according to claim 4, wherein: The fuel electrode also includes a fuel electrode material, which includes nickel (Ni), nickel oxide, cobalt (Co), cobalt oxide, ruthenium (Ru), ruthenium oxide, palladium (Pd), palladium oxide, platinum (Pt), platinum oxide or a combination thereof.
9. The solid oxide battery according to claim 8, wherein: The fuel electrode material is in the form of particles having an average particle size of 0.1 μm to 5 μm.
10. The solid oxide battery according to claim 8, wherein: The fuel electrode includes 30 parts by weight to 70 parts by weight of the fuel electrode material based on 100 parts by weight of the solid oxide electrolyte material.
11. The solid oxide battery according to claim 1, wherein: The solid oxide electrolyte includes yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), or a combination thereof.
12. The solid oxide battery according to claim 1, wherein: The air electrode includes lanthanum strontium manganese oxide (LSM), lanthanum strontium iron oxide (LSF), lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt iron oxide (LSCF), samarium strontium cobalt oxide (SSC), barium strontium cobalt iron oxide (BSCF), bismuth ruthenium oxide or a combination thereof.
13. The solid oxide battery according to claim 12, wherein: The air electrode also includes a solid oxide electrolyte material.
14. The solid oxide battery according to claim 1, wherein: The solid oxide cell is a solid oxide fuel cell (SOFC), a solid oxide electrolyzer (SOEC), or both.
15. A method for manufacturing a solid oxide battery, comprising: A fuel electrode is formed of a composition including hollow particles including a core having a hollow space and a shell including nickel oxide (NiO) particles.
16. The method according to claim 15, wherein: The composition also includes a solid oxide electrolyte material.
17. The method according to claim 16, wherein: The composition also includes a fuel electrode material.
18. The method according to claim 17, wherein: The composition comprises: 30 parts by weight to 70 parts by weight of hollow particles based on 100 parts by weight of the solid oxide electrolyte material; and 30 parts by weight to 70 parts by weight of the fuel electrode material based on 100 parts by weight of the solid oxide electrolyte material.
19. The method according to claim 15, wherein: The step of forming the fuel electrode includes casting the composition and then sintering the cast composition.
20. A solid oxide battery comprising: Solid oxide electrolytes; a fuel electrode located on one side of the solid oxide electrolyte, the fuel electrode comprising a fuel electrode material and hollow particles including a core having an empty space and a shell including nickel oxide (NiO) particles; and An air electrode is located on the other side of the solid oxide electrolyte.
21. The solid oxide battery according to claim 20, wherein: The fuel electrode also includes a solid oxide electrolyte material.
22. The solid oxide battery according to claim 21, wherein The fuel electrode includes 30 to 70 parts by weight of the hollow particles based on 100 parts by weight of the solid oxide electrolyte material.
23. The solid oxide battery according to claim 20, wherein: The fuel electrode material includes nickel (Ni), nickel oxide, cobalt (Co), cobalt oxide, ruthenium (Ru), ruthenium oxide, palladium (Pd), palladium oxide, platinum (Pt), platinum oxide or a combination thereof.
24. The solid oxide battery according to claim 21, wherein The fuel electrode includes 30 parts by weight to 70 parts by weight of the fuel electrode material based on 100 parts by weight of the solid oxide electrolyte material.
25. The solid oxide battery according to claim 20, wherein: The shell contains no other metal oxides.
Citation Information
Patent Citations
Cap unit and container with a cap
KR1020220159245A
Method of manufacturing a template
KR1020230044925A